IDENTIFYING LATE MIOCENE EPISODES OF CONNECTION AND ISOLATION IN THE MEDITERRANEAN-PARATETHYAN REALM USING SR ISOTOPES - Flecker R.; Ellam R.M. (My University, 2006)
After decades of research, the timing and nature of Late Miocene connections between the Mediterranean, Paratethys and the global ocean are still speculative. The hydrologic flux implications of exchange or isolation are central to all hypotheses for generating the major lithological changes that represent the Messinian Salinity Crisis. Moreover, differences in the hydrologic fluxes envisaged are the primary distinction between models. Despite this, these fluxes remain largely unconstrained. This paper describes the basis for using Sr isotope data innovatively combined with salinity data through hydrologic budget modelling to determine the timing and nature of Mediterranean hydrologic connectivity. We examine the hypotheses for three Late Miocene events to illustrate how this approach allows us to test implied hydrologic scenarios and exclude incompatible models. 1) Pre-evaporite restriction of the Mediterranean; 2) the initiation of salt precipitation; 3) connection between the Sea of Marmara and both Paratethys and the Mediterranean during the Messinian. This process suggests that the Atlantic-Mediterranean exchange was significantly reduced up to three million years before evaporite precipitation. It also indicates that end-member hypotheses for initiating salt precipitation in the Mediterranean (desiccation and connected basin models) are inconsistent with Sr isotope data. A contrasting model where evaporite formation was triggered by Atlantic transgression into a strongly evaporation-dominated Mediterranean is shown to be more compatible with available datasets. The application to Sea of Marmara samples indicates that salinity changes in the basin were not caused by changes to the amount of inflow from either Paratethys or the Mediterranean. Other possible as yet untested applications important for constraining different aspects of the Messinian Salinity Crisis are highlighted. © 2006 Elsevier B.V. All rights reserved.
Keywords: FAUNA; LITHOLOGY; MESSINIAN SALINITY CRISIS; OCEANIC-EXCHANGE; SALINITY; SR ISOTOPES; Messinian; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский